Hades : god of the underworld - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek god Hades, god of the underworld.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
4.5
3-6.
3-6
Keywords: Hades, -- (Greek deity -- Juvenile literature; Hades -- (Greek deity); Hades -- (Greek deity); Mythology, Greek -- Juvenile literature; Mythology, Greek; Greek mythology